Предмет: Алгебра,
автор: vvolf
Докажите, что если x>0, y>0 и z>0, то ((x^2)/y)+((y^2)/z)>=4*(x-z)
Ответы
Автор ответа:
0
Так просто короче было)))
x^2*z+y^3-4xyz+4y(z^2)=z(x^2-4xy)+y^3+4y(z^2)=z*(x-y)^2+y^3+4y(z^2)-zy^2
Оставим только y^3+4y(z^2)-zy^2
y*(y^2-zy+4z^2)=y[(y-2z)^2+3yz]
Короче всё положительно, всё доказано.
Похожие вопросы
Предмет: Қазақ тiлi,
автор: arsenjob2
Предмет: Математика,
автор: ayiarobloxxd
Предмет: Алгебра,
автор: asemaaminaokeeva
Предмет: Математика,
автор: iren1952
Предмет: Алгебра,
автор: dom1nikano